Metallic material
Patent Information
- Application Number
- JP2023149369
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-14
- Publication Date
- 2025-03-27
Smart Images

Figure 2025042390000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a metal material having an oxide film formed on the surface of the metal by plasma electrolytic oxidation. [Background technology]
[0002] 2. Description of the Related Art Conventionally, plasma electrolytic oxidation (hereinafter also referred to as "PEO") treatment has been used as a method for forming a coating on the surface of a metal.
[0003] This PEO treatment is a type of anodizing process in which a metal is immersed in an electrolyte and a high voltage is applied to the metal, generating a plasma discharge between the metal and the electrolyte, forming an oxide film on the surface of the metal.
[0004] For example, the present applicant has proposed a method for forming a film using PEO treatment, which includes at least the steps of forming a film on the surface of a metal by immersing the metal as an anode in an electrolytic solution containing a water-soluble compound and generating a plasma discharge between the metal and the electrolytic solution, and heat treating the metal on which the film has been formed (see Patent Document 1). With this method, it is possible to form a highly corrosion-resistant film on the surface of the metal, and a metal material with excellent corrosion resistance can be obtained. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2016-156036 A Summary of the Invention [Problem to be solved by the invention]
[0006] Here, the method described in the above Patent Document 1 can improve the corrosion resistance of metals, but does not fully consider the wear resistance of metals. For example, there is a problem that the wear resistance cannot be sufficiently improved in metals with poor wear resistance, such as magnesium and magnesium alloys.
[0007] Therefore, the present invention has been made in consideration of the above-mentioned problems, and aims to obtain a metal material having excellent wear resistance and an oxide film formed on the metal surface by plasma electrolytic oxidation. [Means for solving the problem]
[0008] The inventors conducted further research into oxide films formed on metal surfaces by plasma electrolytic oxidation and discovered that the wear resistance of the oxide film correlates with the proportion of crystalline matter in the oxide film (degree of crystallinity), leading to the completion of the present invention.
[0009] In order to achieve the above object, the metal material of the present invention is a metal material having an oxide film formed on a metal surface by plasma electrolytic oxidation, and based on an X-ray diffraction spectrum of the oxide film measured by an X-ray diffraction method, the metal material has a surface roughness of 0.01 mm, and the surface roughness of the metal material is determined by the following mathematical formula (1): Crystallinity of oxide film = crystalline area / (crystalline area + amorphous area) (1) The oxide film has a crystallinity of 0.5 or more as calculated by the above formula: Effect of the Invention
[0010] According to the present invention, it is possible to obtain a metal material having an oxide film formed on the surface of the metal by plasma electrolytic oxidation and having excellent wear resistance. [Brief description of the drawings]
[0011] [Figure 1] 1 is a cross-sectional view showing a metal material on which an oxide film is formed according to an embodiment of the present invention. [Diagram 2] 1A to 1C are diagrams for explaining a method for forming an oxide film by plasma electrolytic oxidation. [Diagram 3]FIG. 2 is a diagram showing an X-ray diffraction spectrum of the oxide film of the metal material produced in Example 1. [Figure 4] FIG. 2 is a diagram showing the relationship between the degree of crystallinity and the wear depth in the oxide films of the metal materials produced in the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. However, the present invention is not limited to the following embodiment.
[0013] FIG. 1 is a cross-sectional view showing a metal material having an oxide film formed thereon according to an embodiment of the present invention.
[0014] As shown in FIG. 1, the metallic material 1 of this embodiment includes a metallic substrate 2 and an oxide film 3 formed on the surface of the metallic substrate 2.
[0015] The metal for forming the metal substrate 2 is not particularly limited as long as it is capable of applying a voltage in the PEO treatment, and examples of the metal that can be used include magnesium, aluminum, zinc, manganese, calcium, yttrium, silicon, titanium, iron, and alloys thereof.
[0016] The oxide film 3 is a porous ceramic film formed on the surface of the metal substrate 2 by applying a high voltage to the metal substrate 2 while the metal substrate 2 is immersed as an anode in an electrolytic solution containing phosphate and silicate, thereby generating a plasma discharge between the metal substrate 2 and the electrolytic solution. In other words, the oxide film 3 is a PEO film formed on the surface of the metal substrate 2 by PEO treatment. Therefore, the oxide film 3 contains at least one oxide selected from the metal components (the metals forming the metal substrate 2) contained in the metal substrate 2 and the electrolytic solution components (phosphate, silicate, etc.) used in the PEO treatment. Specifically, the oxide film 3 contains at least one of a compound containing the metal component and oxygen, a compound containing the electrolytic solution components and oxygen, and a compound containing the metal component, the electrolytic solution components, and oxygen.
[0017] Here, in the metal material 1 according to this embodiment, the crystallinity of the oxide film 3 is specified to be 0.5 or more. The crystallinity of the oxide film 3 correlates with the wear resistance of the oxide film 3, as described in the following examples. If the crystallinity of the oxide film 3 is within the above range, high wear resistance is ensured. In this specification, the crystallinity of the oxide film 3 refers to the ratio (proportion) of the crystalline matter in the oxide film 3 [with respect to the total of the crystalline matter and the non-crystalline matter (amorphous phase, non-crystalline matter) in the oxide film 3 (the entire oxide film 3)]. Specifically, the crystallinity of the oxide film 3 refers to a value calculated by the following mathematical formula (1) (hereinafter also referred to as "crystallinity (1)"). [Formula] Crystallinity of oxide film = crystalline area / (crystalline area + amorphous area) (1).
[0018] In formula (1), the "crystalline area" and the "amorphous area" are calculated from the X-ray diffraction spectrum of the oxide film 3 measured by thin film X-ray diffraction (X-ray diffraction: XRD, parallel beam method). Examples of the calculation method include the method described in the following examples. When the oxide film 3 contains multiple crystalline substances (multiple crystalline substances are identified from the X-ray diffraction spectrum), the "crystalline area" refers to the sum of the areas of the diffraction peaks of the multiple crystalline substances. Similarly, when the oxide film 3 contains multiple amorphous substances (multiple amorphous substances are identified from the X-ray diffraction spectrum), the "amorphous area" refers to the sum of the areas of the diffraction peaks of the multiple amorphous substances.
[0019] The degree of crystallinity (1) of the oxide coating film 3 specified as above is a calculated value (analytical value) based on the X-ray diffraction spectrum, and is not a quantitative value (quantitative analysis value) such as a molar ratio, volume ratio, or mass ratio of crystals or amorphous matter in the oxide coating film 3.
[0020] The crystallinity (1) of the oxide film 3 is 0.5 or more, preferably 0.55 or more, more preferably 0.6 or more, and even more preferably 0.7 or more, from the viewpoint of improving the wear resistance of the metal material 1 (the oxide film 3 formed on the surface thereof).
[0021] The crystallinity (1) of the oxide film 3 can be adjusted (specified) to the above range by, for example, adjusting the composition of the electrolyte (type and concentration of electrolyte components) and the duty ratio and processing time in the PEO treatment step described later. Specifically, in order to adjust (specify) the crystallinity (1) of the oxide film 3 to the above range, it is considered effective to prepare an oxide film with a high crystallinity by increasing the discharge energy during PEO treatment. Examples of means for increasing the discharge energy include increasing the electrolysis voltage in the PEO treatment step, extending the pulse width (duty ratio) when using pulse electrolysis, and increasing the conductivity of the electrolyte in the electrolyte preparation step described later. However, these means affect each other, and if only a specific parameter is made too large (or small), side effects such as the oxide film not growing or the oxide film collapsing due to discharge may occur.
[0022] The phosphate in the electrolyte is not particularly limited, but for example, sodium phosphate, potassium phosphate, sodium polyphosphate, etc. can be used. These may be used alone or in combination of two or more. The concentration of the phosphate in the electrolyte is preferably 15 mmol / L (mM) or more and 50 mmol / L or less, more preferably 20 mmol / L or more and 30 mmol / L or less.
[0023] The silicate in the electrolyte is not particularly limited, but for example, sodium metasilicate nonahydrate, sodium metasilicate anhydrous, sodium silicate, potassium silicate, etc. can be used. These may be used alone or in combination of two or more. The concentration of the silicate in the electrolyte is preferably 15 mmol / L or more and 50 mmol / L or less, more preferably 20 mmol / L or more and 30 mmol / L or less.
[0024] In the electrolytic solution containing phosphate and silicate, the molar ratio of phosphate to silicate is preferably phosphate:silicate = 1: 2 to 2: 1. By carrying out the PEO treatment using an electrolytic solution in which the molar ratio of phosphate to silicate is within the above range, it is possible to form an oxide coating 3 on the surface of the metal substrate 2 that has a crystallinity (1) within the above range (i.e., has high abrasion resistance).
[0025] The total concentration of the phosphate and silicate in the electrolytic solution is preferably 15 mmol / L or more and 100 mmol / L or less, and more preferably 20 mmol / L or more and 80 mmol / L or less. This is because if the concentration is less than 15 mmol / L, the metal substrate 2 itself may dissolve due to the high electrolytic voltage required, and if the concentration is more than 100 mmol / L, the phosphate may not dissolve easily and the stability of the electrolytic solution may be poor. In other words, by setting the total concentration of the phosphate and silicate in the above range, it is possible to stably form the oxide film 3 during electrolytic treatment.
[0026] The electrolyte may contain a citrate such as sodium citrate, lithium citrate, potassium citrate, or calcium citrate, or an organic acid salt such as sodium tartrate or sodium acetate.
[0027] The concentration of the organic acid salt in the electrolytic solution is preferably 30 mmol / L or less, and more preferably 1 mmol / L to 5 mmol / L. This is because if the concentration is greater than 30 mmol / L, it may be difficult to form the oxide film 3. That is, by setting the concentration of the organic acid salt to 30 mmol / L or less, it becomes possible to stably form the oxide film 3 during electrolysis.
[0028] The electrolyte may contain an alkaline agent (pH adjuster) such as potassium hydroxide or sodium hydroxide. The concentration of the alkaline agent in the electrolyte is not particularly limited and may be appropriately adjusted according to the pH of the electrolyte described below, but is preferably 50 mmol / L or more and 500 mmol / L or less, for example.
[0029] From the viewpoint of suppressing the self-dissolution reaction of the metal material in the electrolytic solution, the pH of the electrolytic solution is preferably in the range of 12.5 to 14. In this embodiment, the above alkaline agent is added to the electrolytic solution so that the pH of the electrolytic solution falls within the above range.
[0030] Next, a method for producing a metal material having an oxide film formed by plasma electrolytic oxidation on the surface of the metal according to an embodiment of the present invention will be described. FIG. 2 is a diagram for explaining a method for forming an oxide film by plasma electrolytic oxidation. This oxide film forming method includes an electrolytic solution preparation step and a PEO treatment step.
[0031] <Electrolytic solution preparation step> First, phosphates such as sodium phosphate and silicates such as sodium metasilicate nonahydrate are added to water as a solvent, and, if necessary, organic acid salts such as trisodium citrate and alkaline agents such as sodium hydroxide are added, and the mixture is stirred and mixed to be uniform to prepare an electrolytic solution. In addition, a chelating agent such as EDTA may be added if necessary (step S1).
[0032] <PEO treatment step> Next, a metal substrate 2 such as magnesium is immersed in the electrolytic solution (step S2), and a high voltage is applied to the metal substrate 2 while the metal substrate 2 is immersed in the electrolytic solution, thereby generating plasma discharge between the metal substrate 2 and the electrolytic solution to form an oxide film 3 on the surface of the metal substrate 2 (step S3). Note that the PEO treatment may be performed while stirring the electrolytic solution.
[0033] As the PEO treatment method, a pulse electrolysis method, a direct current electrolysis method, an alternating current electrolysis method, etc. using the metal substrate 2 as an anode can be used, but from the viewpoint of forming an oxide film uniformly, it is preferable to use the pulse electrolysis method.
[0034] As the electrolysis voltage, the maximum voltage may be equal to or higher than the discharge (arc discharge) voltage, but from the viewpoint of improving the stability of the PEO treatment, it is preferably set to 80V to 800V.
[0035] When using pulse electrolysis, from the viewpoints of energy efficiency and forming a uniform oxide film, it is preferable to set the frequency to 100 Hz to 10,000 Hz and the duty ratio to 0.05 or more and 0.5 or less.
[0036] The PEO treatment time can be appropriately changed from the viewpoints of ensuring the wear resistance of the oxide coating 3 and energy efficiency, and can be set, for example, from 1 to 120 minutes, and is preferably set to 1 to less than 90 minutes.
[0037] Moreover, examples of materials that can be used to form the cathode when carrying out the PEO treatment include stainless steel, graphite, copper, titanium, and platinum.
[0038] When the PEO treatment is started, an electrolytic reaction occurs in the metal substrate 2, which is the anode, and first, the metal forming the metal substrate 2 reacts with chemical species containing oxygen in the water to form a thin oxide film (barrier layer) on the surface of the metal substrate 2. Then, light is emitted within the oxide film due to the electron avalanche phenomenon.
[0039] Next, an arc discharge is initiated, and the heat of the arc discharge causes melting on the metal surface, causing oxides of the metal components and electrolyte components (i.e., phosphates and silicates) to grow on the oxide film, and a porous ceramic film (i.e., oxide film 3) having a thickness of several μm to several tens of μm and containing metal, oxygen, phosphates, silicates, etc. is formed on the surface of the metal substrate 2.
[0040] Here, in the metal material of this embodiment, the crystallinity (1) of the oxide film 3 calculated based on the above formula (1) is 0.5 or more, and therefore an oxide film 3 with high wear resistance is formed on the surface of the metal substrate 2.
[0041] In addition, in the metal material of this embodiment, there is no need to use potassium fluoride or zirconium compounds, which are difficult to handle, as electrolyte components for the plasma electrolytic oxidation used to form the oxide film 3, so that the oxide film 3 having high wear resistance can be easily formed on the surface of the metal substrate 2.
[0042] As described above, a wear-resistant metal material 1 with an oxide film 3 formed on the surface of the metal substrate 2 shown in FIG. 1 can be produced.
Example
[0043] Hereinafter, the present invention will be described based on examples. It should be noted that the present invention is not limited to these examples, and these examples can be modified and changed based on the gist of the present invention, and they are not excluded from the scope of the present invention.
[0044] (Examples and Comparative Examples) <Preparation of Electrolyte Solution> Sodium phosphate (manufactured by Kishida Chemical Co., Ltd., indicated as "Na3PO4" in Table 1), sodium metasilicate nonahydrate (manufactured by Kishida Chemical Co., Ltd., indicated as "Na2SiO3" in Table 1), trisodium citrate (manufactured by Kishida Chemical Co., Ltd., indicated as "Na3Citrate" in Table 1), and sodium hydroxide (manufactured by Kishida Chemical Co., Ltd., indicated as "NaOH" in Table 1) were added to water as a solvent at the respective concentrations shown in Table 1, and stirred until uniform to prepare an electrolyte solution.
[0045] <PEO Treatment> Next, a magnesium alloy plate made of a magnesium alloy (MDC-AXS620) added with aluminum or zinc and having a surface area of 18 cm 2 was used as the anode, and a stainless steel tank made of SUS304 and having a surface area of 1300 cm 2 was used as the cathode. With the magnesium alloy plate immersed in the prepared electrolyte solution, a high voltage was applied to the magnesium alloy plate for the treatment time shown in Table 1 to generate plasma discharge between the magnesium alloy plate and the electrolyte solution, and an oxide film with a thickness of about 10 μm was formed on the surface of the magnesium alloy plate to produce the metal material of this example.
[0046] Note that the PEO treatment was performed with the electrolysis voltage set to 300 V, the frequency set to 167 Hz, and the duty ratio shown in Table 1.
[0047] <Evaluation of crystallinity of oxide film> The X-ray diffraction intensity of the oxide film formed on the surface of each of the metal materials produced in the examples and comparative examples was measured under the following conditions using thin film X-ray diffraction (X-ray diffraction: XRD, parallel beam method), and the crystallinity of the oxide film was calculated based on the following method. The results are shown in Table 1. The X-ray diffraction spectrum measured in Example 1 is shown in Figure 3.
[0048] (XRD measurement conditions) Device name: Rigaku Corporation, SmartLab X source target: Cu / K α1 (λ=0.154056nm) Output: 45kV, 200mA ·Incidence angle: 0.5° Scan speed: 2.0° / min Step: 0.02° Measurement range: Diffraction angle 2θ=5°~80° Analysis software: Rigaku Corporation, SmartLab Studio II Under the above XRD measurement conditions, the X-ray diffraction spectra of the oxide films of each metal material were measured.
[0049] (Method of calculating crystallinity from X-ray diffraction spectrum) The method of calculating the crystallinity of the oxide film will be described below using the X-ray diffraction spectrum measured in Example 1 shown in FIG. 3 as an example. First, the area of each diffraction peak of MgO and / or Mg2SiO4 as the crystalline material shown in Table 1 and the amorphous phase (non-crystalline material) as the non-crystalline material was calculated. The area of each diffraction peak was calculated by fitting the actual value of the X-ray diffraction spectrum (shown as "actual spectrum" in FIG. 3) using a pseudo-Voigt function and performing background (BG) processing using the above-mentioned analysis software attached to the device. In FIG. 3, the spectrum after the above-mentioned processing is shown as "processed spectrum". In addition, in FIG. 3, the baseline spectrum in the "processed spectrum" is shown as "baseline spectrum", the spectrum of the amorphous phase (non-crystalline material) is shown as "amorphous spectrum", and the spectrum of the crystal is shown as "crystal spectrum". The "crystal spectrum" refers to the spectrum obtained by subtracting the "amorphous spectrum" from the "processed spectrum".
[0050] Next, the "crystalline area" and the "amorphous area" described in the above formula (1) were calculated as follows. The "crystal area" was calculated as the total area surrounded by the "crystal spectrum" and the "baseline spectrum." The "amorphous area" was calculated as the total area surrounded by the "amorphous spectrum" and the "baseline spectrum".
[0051] Finally, the crystallinity of the oxide film was calculated by substituting the values of the "crystalline area" and "amorphous area" calculated above into the above formula (1).
[0052] From the X-ray diffraction spectrum shown in Fig. 3, the crystalline substances in the oxide films of the metal materials produced in the examples and comparative examples are considered to be oxides and compounds such as MgO (magnesia), Al2O3 (alumina), SiO2 (silica), MgSiO3 (enstatite), Mg2SiO4 (forsterite), Al2SiO4(OH,F)2 (topaz), MgO·Al2O3 (spinel), (Mg,Fe)2SiO4 (olivine), etc. Also, the non-crystalline substances (amorphous substances) in the oxide films are considered to be, for example, Mg3(PO4)2·nH2O (magnesium phosphate hydrate), mixtures containing SiO2, Na2O, CaO, etc. (soda glass, borosilicate glass), etc.
[0053] <Wear resistance evaluation> The wear resistance of the oxide film formed on the surface of each of the metal materials produced in the examples and comparative examples was evaluated using a friction tester (manufactured by Bruker, product name: UMT-TriboLab).
[0054] Specifically, a tungsten carbide (WC) ball with a diameter of 9.525 mm (3 / 8 inch) was first brought into contact with the oxide film surface of the prepared metal material, and while pressing the ball so that a load of 10 N was applied to the contact surface, the ball was moved at a stroke length of 1 mm at 90 reciprocations per minute (test time: 10 minutes, speed: 1.5 Hz).
[0055] After 900 reciprocating friction tests, the wear depth [μm] of the metal material was measured using a shape analysis laser microscope (Keyence Corporation, product name: VK-X250). The measurement was performed three times, and the average value was calculated as the wear depth [μm]. The results are shown in Table 1. The relationship between the calculated crystallinity and the wear depth is shown in Figure 4.
[0056] [Table 1]
[0057] As shown in Table 1 and Figure 4, in a metal material having an oxide film formed on the surface of a magnesium alloy by PEO treatment using an electrolyte containing phosphate and silicate, in Comparative Example 1 in which the crystallinity of the oxide film is 0.253, the wear depth of the metal material is greater than the thickness of the oxide film (about 10 μm), and the wear penetrates the oxide film to the surface of the magnesium alloy, indicating that the metal material has very poor wear resistance.
[0058] On the other hand, in each of the Examples in which the crystallinity of the oxide film was 0.5 or more, the wear depth of the metal material was extremely small and the wear resistance was significantly superior compared to Comparative Example 1. Furthermore, a comparison of the Examples shows that the greater the crystallinity of the oxide film, the higher the wear resistance.
[0059] The above results show that in the oxide film formed on the surface of a metal by PEO treatment, the crystallinity calculated by the above formula (1) based on the X-ray diffraction spectrum correlates with the wear resistance, and that a crystallinity of 0.5 or more ensures high wear resistance. [Industrial Applicability]
[0060] As described above, the present invention is suitable for metal materials having an oxide film formed on the surface of the metal by plasma electrolytic oxidation treatment. [Explanation of symbols]
[0061] 1 Metal materials 2 Metal Substrate 3. Oxide film
Claims
1. A metal material having an oxide film formed on a surface of the metal by plasma electrolytic oxidation, Based on the X-ray diffraction spectrum of the oxide film measured by an X-ray diffraction method, the following formula (1): Crystallinity of oxide film = crystalline area / (crystalline area + amorphous area) (1) The metal material is characterized in that the crystallinity of the oxide film calculated by the above formula is 0.5 or more.
2. 2. The metallic material according to claim 1, wherein the oxide film contains at least one oxide selected from the metal and components of an electrolyte used in the plasma electrolytic oxidation.
3. 3. The metallic material according to claim 1, wherein the metal is magnesium or a magnesium alloy.
4. 3. The metallic material according to claim 1, wherein an electrolyte used in the plasma electrolytic oxidation contains a phosphate and a silicate.
Citation Information
Patent Citations
Coating formation method
JP2016156036A